Dizzy People Perform No Worse at a Motor Imagery Task Requiring Whole Body Mental Rotation; A Case-Control Comparison - Wallwork, Sarah B.; Butler, David S.; Moseley, G Lorimer (Frontiers in Human Neuroscience, 2013)
We wanted to find out whether people who suffer from dizziness take longer than people who do not, to perform a motor imagery task that involves implicit whole body rotation. Our prediction was that people in the ‘dizzy’ group would take longer at a left/right neck rotation judgment task but not a left/right hand judgment task, because actually performing the former, but not the latter, would exacerbate their dizziness. Secondly, we predicted that when dizzy participants responded to neck rotation images, responses would be greatest when images were in the upside-down orientation; an orientation with greatest dizzy-provoking potential. To test this idea, we used a case-control comparison design. One hundred and eighteen participants who suffered from dizziness and 118 age, gender, arm pain and neck pain matched controls took part in the study. Participants undertook two motor imagery tasks; a left/right neck rotation judgment task and a left/right hand judgment task. The tasks were completed using the Recognise program; an on-line reaction time task program. Images of neck rotation were shown in four different orientations; 0°, 90°, 180° and 270°. Participants were asked to respond to each ‘neck’ image identifying it as either ‘right neck rotation’ or a ‘left neck rotation’, or for hands, a right or a left hand. Results showed that participants in the ‘dizzy’ group were slower than controls at both tasks (p= 0.015), but this was not related to task (p= 0.498). Similarly, ‘dizzy’ participants were not proportionally worse at images of different orientations (p= 0.878). Our findings suggest impaired performance in dizzy people, an impairment that may be confined to motor imagery or may extend more generally.